Biochar and syngas from wet torrefaction of oil palm empty fruit bunches and palm oil mill effluent: A renewable energy approach - Mohamad Aziz N.A.; Ling Y.K.; Mohamed H.; Zainal B.S.; Zaman H.B.; Alsultan A.G. (Institute of Physics, 2025)
Palm oil mill effluent (POME) and oil palm empty fruit bunches (EFB) constitute the highest waste generated in the mill. This study investigates thermochemical approaches, specifically wet torrefaction and gasification, aiming to transform these wastes into higher-value products such as biochar. Wet torrefaction was initially applied to EFB and POME at 200 C, with a heating rate of 5 C/min for 30-min residence time under nitrogen-inert conditions, resulting in a solid yield of 82%. This process led to a notable increase in the heating value of raw EFB by 30.6%, from 17.3 to 22.6 MJ/kg. Subsequently, the product underwent gasification at various temperatures ranging from 600 to 800 C, with a constant heating rate of 10 C/min, gas flow rate of 20 ml/min, and a retention time of 30 min. The gasification reaction improved the solid yield and resulted in the generation of liquid products and syngas. The results indicated that 45-59% of biochar, 12-17% of bio-oil, and 30-39% of syngas were produced. The syngas composition, determined using gas chromatography, revealed the presence of CO2, H2, CH4, and CO. The solid product, characterised by a higher heating value, is a viable alternative for solid fuel. The findings suggested that both wet torrefaction and the gasification process have the potential to address the abundance of palm mill waste issues and offer an alternative approach for utilising and generating energy within the mill. ? Published under licence by IOP Publishing Ltd.